Enhancement of the Yield of Ammonia by Hydrogen‐Sink Effect during Plasma Catalysis. Issue 4 (19th December 2019) - Shah, Javishk; Gorky, Fnu; Psarras, Peter; Seong, Bomsaerah; Gómez‐Gualdrón, Diego A.; Carreon, Maria L.
Abstract: Plasma‐catalytic ammonia synthesis has been known since the early 1900s, but only until now efforts to optimize catalysts for this purpose are emerging. Here, we investigate various transition metals, low‐melting‐point metals, and gallium‐rich alloy catalysts for their activity towards ammonia production under a plasma environment. The best three pure metal catalysts were Ni, Sn and Au, which are not traditional catalysts for the current industrial ammonia synthesis. The ammonia yields for these catalysts were 34 %, 29 %, and 19 %, respectively. Synergistic effects were detected when employing alloys, as some alloys presented ∼25–50 % higher yields than their constituent metals. The employed metals were classified into two categories. Category I metals (Cu, Ag, Au and Fe), which are nitrophobic (excluding Fe, the Haber‐Bosch catalyst) and poor hydrogen sinks. For these metals, the measured concentration of Hα in the gas phase tended to correlate inversely with ammonia yield and directly with the H binding strength on the catalyst surface. Category II metals (Ga, In, Sn and Ni), which are good hydrogen sinks, tend to have a lower concentration of Hα in the gas phase than that of category I metals, which is consistent with their expected sink behavior. For these metals, the concentration of Hα correlates with ammonia yield. Plasma characterization experiments and DFT calculations suggest that the higher performance of Ni and Sn is related to the benefit of dissolving hydrogen to slow down H recombination, which is a feature that could be potentially optimized in future studies by rationally altering the catalyst composition. Abstract : Plasma catalysis : The effect of several transition metals and gallium‐rich alloys on the ammonia yield when employed as catalysts in non‐thermal plasma environment were investigated. In the case of pure metal catalysts, Ni, Sn, Au being unconventional catalysts, surpassed the performance of other traditional pure metal catalysts such as Fe. Metals were divided in two categories based on our experimental observations: nitrophobic and hydrogen sinks. We suggest that the optimum combination of metals from these categories can lead to unprecedented ammonia yields.